MILITARY SECURITY IN THE AGE OF ARTIFICIAL INTELLIGENCE - Radionova , Iryna (Collection of scientific papers «ΛΌГOΣ», 2023)
National and international policies in the field of artificial intelligence (AI) must take into account its potential transformative potential, dynamics and dangers. The policy of leading countries in the field of AI is beginning to be formalized and structured at the national level. Most of the developed countries today already have basic plans for the development of AI. They can be formalized as integral national strategies, or they can exist in the form of a number of documents devoted to separate areas of activity. Applicants for the role of world leaders in the field of AI focus attention on the security dimensions of its application. One of these dimensions is military security. AI (and AI-enhanced autonomous weapons systems) can be applied and bring maximum potential military benefits at a tactical, operational and strategic level.